Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
Answer:
b) -10
Step-by-step explanation:
x^2 + 3x + k = (x - 2)(x - a)
(x - 2)(x - a) = x^2 - 2x - ax + 2a = x^2 + [-2 - a)x] + 2a
-2 - a = 3
2a = k
a = -5
k = 2(-5) = -10
Answer: b) -10
Answer:
GET READY FOR FIGHT !!!!!
Step-by-step explanation:
*Intense music in background*
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.